Are Empowered Employees More Proactive? The Contingency of How They Evaluate Their Leader - Yin, Kui; Xing, Lu; Li, Can; Guo, Yungui (Frontiers in Psychology, 2017)
Finding ways to enhance employee proactive behavior is a focal concern for academics and practitioners. Previous studies have found a positive association between empowering leadership and proactive behavior. However, these studies lack elaboration on mechanisms and do not rule out the effect of employees’ proactive personality during empirical testing. We investigate empowering leadership from individual perspective due to the variation of empowerment levels even in the same team. Our research proposes a more elaborated theoretical model that explains why, and when, empowering leadership might promote employee proactive behavior. Specifically, we examine mediating mechanisms based on social cognitive theory and propose trust in leader competency as boundary condition. Using a sample of 280 leader–follower dyads from a large state-owned Chinese company, our results revealed that (1) empowering leadership was positively related to proactive behavior, with role breadth self-efficacy acting as a mediator for this relationship; (2) employees’ trust in leader competency moderated both the empowering leadership–subordinate proactive behavior relationship and the mediating effect of role breadth self-efficacy, such that the empowering leadership–subordinate proactive behavior relationship was weaker, and the mediating effect of role breadth self-efficacy was stronger, for employees with high levels of trust in leader competency.